Transcutaneous immunization of Streptococcus suis bacterin using dissolving microneedles. (February 2017) - Hsueh, Kai-Jen; Chen, Mei-Chin; Cheng, Li-Ting; Lee, Jai-Wei; Chung, Wen-Bin; Chu, Chun-Yen
Highlights: Dissolving microneedle vaccine containing S. suis 2 bacterin was evaluated in mice. Microneedles induce TH 1-type cytokine production, antibody response, and strong T cell proliferation. Single-dose microneedle vaccination provides higher protection rate in challenge test than intramuscular vaccination. Single-dose microneedle vaccination maintains TH1-type antibody levels for up to 7 months. Abstract: Vaccine delivery using microneedle (MN) patches is an easy, safe and painless alternative to traditional needle injections. In this study, we examined whether MN patches can enhance the efficacy of a Streptococcus suis serotype 2 ( S. suis 2) vaccine in a mouse model. Results showed that MNs can reach 200–250 μm into the skin, a depth beneficial for targeted delivery of antigens to antigen-presenting cells in the epidermis and dermis. Vaccination with prime-boost of MN induced higher levels of IgG2a antibody titer, T cell proliferation, and TH 1 cytokines (IFN-γ and IL-12) as compared to intramuscular (IM) injection. In addition, single dose MN vaccination better protected mice against lethal challenge than IM vaccination. MN vaccination also conferred long-term IgG2a antibody against S. suis 2 bacteria presence for up to 7 months. Taken together, these data showed that vaccine delivery by MNs results in superior immune response and protection rate when compared to IM injections.